An Adaptive Moving Mesh Method for Two-Dimensional Relativistic Hydrodynamics (Communications in Computational Physics, 2012)
This paper extends the adaptive moving mesh method developed by Tangand Tang [36] to two-dimensional (2D) relativistic hydrodynamic (RHD) equations.The algorithm consists of two "independent" parts: the time evolution of the RHDequations and the (static) mesh iteration redistribution. In the first part, the RHDequations are discretized by using a high resolution finite volume scheme on the fixedbut nonuniform meshes without the full characteristic decomposition of the governing equations. The second part is an iterative procedure. In each iteration, the meshpoints are first redistributed, and then the cell averages of the conservative variablesare remapped onto the new mesh in a conservative way. Several numerical examplesare given to demonstrate the accuracy and effectiveness of the proposed method.